Clinical neuroscience an illustrated colour text - Johns, Paul (Illustrated colour text, 2014)
Provides a clear and readable introduction to the central concepts of clinical neuroscience. This book deals with fundamental areas of neuroscience required for a sound understanding of brain disease.